2017
DOI: 10.1016/j.canlet.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal formulation of anthocyanidins against multiple cancer types

Abstract: Over the last two decades, berries and berry bioactives, particularly anthocyanins and their aglycones anthocyanidins (Anthos) have demonstrated excellent anti-oxidant, anti-proliferative, apoptotic and anti-inflammatory properties. However, their physicochemical and pharmacokinetic limitations such as, low permeability, and poor oral bioavailability are considered as unfavorable properties for development as drugs. Therefore there is a need to develop systems for efficient systemic delivery and robust bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 68 publications
(91 reference statements)
3
134
0
3
Order By: Relevance
“…Milk EVs have been extensively studied for their biological functions upon consumption (Agrawal et al., ; Aqil et al., ; Aqil, Munagala, Jeyabalan, Agrawal, & Gupta, ; Arntz et al., ; Badawy, El‐Magd, & AlSadrah, ; Leiferman et al., ; Matsuda & Patel, ; Munagala, Aqil, Jeyabalan, & Gupta, ; Munagala et al., ; Oliveira et al., , 2017) and numerous studies have reported that milk EVs are bioaccessible (survive digestion; Benmoussa et al., ; Kahn et al., ; Liao et al., ; Rani et al., ; Shandilya, Rani, Onteru, & Singh, ; Vashisht, Rani, Onteru, & Singh, ) and bioavailable (Le Doare et al., ; Wang et al., ; Zempleni, ; Zempleni et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Milk EVs have been extensively studied for their biological functions upon consumption (Agrawal et al., ; Aqil et al., ; Aqil, Munagala, Jeyabalan, Agrawal, & Gupta, ; Arntz et al., ; Badawy, El‐Magd, & AlSadrah, ; Leiferman et al., ; Matsuda & Patel, ; Munagala, Aqil, Jeyabalan, & Gupta, ; Munagala et al., ; Oliveira et al., , 2017) and numerous studies have reported that milk EVs are bioaccessible (survive digestion; Benmoussa et al., ; Kahn et al., ; Liao et al., ; Rani et al., ; Shandilya, Rani, Onteru, & Singh, ; Vashisht, Rani, Onteru, & Singh, ) and bioavailable (Le Doare et al., ; Wang et al., ; Zempleni, ; Zempleni et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Twenty‐one studies involving milk EVs from humans, rat, camels, and most often cow milks reported milk EVs bioactivity in vitro on cells (Admyre et al., ; Aqil et al., , ; Badawy et al., ; Golan‐Gerstl et al., ; Hock et al., ; Martin et al., ; Matsuda & Patel, ; Mobley et al., ; Munagala et al., ; Naslund et al., ; Qin et al., ; Vashisht et al., ; Yu et al., ) and in vivo in animal models (Agrawal et al., ; Aqil et al., , ; Badawy et al., ; Leiferman et al., ; Munagala et al., ; Munagala et al., ; Somiya et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Additional mechanistic studies are planned to clearly elucidate the specifics of the pathway(s). We also plan to examine the effects of These results correspond with our previous findings for other drugs delivered using exosomes [104]. Therefore, the results support our initial hypothesis that exosomal delivery will improve Anthos potency presumably due to increased bioavailability and stability of Anthos.…”
Section: Impact Of Milk-derived Exoanthos Vs Colostrum-derived Exoansupporting
confidence: 83%
“…These results suggest that colostrum exosomes possess no in vitro toxicity to the normal cells and that they possess an intrinsic activity against colon cancer cells specifically. This "internal payload" effect is an exciting feature that our lab has also identified for other cancers such as breast and lung cancers [104].…”
Section: Anti-proliferative Effects Of Exosomes Alone On Colon Cancermentioning
confidence: 66%
“…However, due to their poor bioavailability and retention, these compounds cannot be used efficiently. In a recent study, Munagala et al attempted to encapsulate these compounds in exosomal lumen and showed enhanced therapeutic effect in cancer cells and in lung cancer xenografts in nude mice, suggesting the benefit of using exosomes as drug delivery vehicles (Munagala et al, 2017). …”
Section: Theranostics Applications Of Exosomes In Lung Cancermentioning
confidence: 99%